A DECISION SUPPORT SYSTEM MODEL FOR SELECTING SCHOLARSHIP RECIPIENTS USING A COMBINATION OF THE AHP AND TOPSIS METHODS - Thamrin, Musdalifa (Yayasan Nusantara Hasana Berdikari, 2025)
The selection of scholarship recipients is a critical process in determining which students are eligible for educational assistance based on specific criteria. The selection process, which is still conducted manually, often leads to issues such as subjectivity, inaccurate assessments, and significant time consumption. This study aims to develop a Decision Support System model for scholarship recipient selection using a combination of the Analytical Hierarchy Process (AHP) and the Technique for Order Preference by Similarity to Ideal Solution (TOPSIS). The AHP method is used to determine the priority weights of each criterion, while the TOPSIS method is used to rank scholarship candidates based on the highest preference scores. The results of the study indicate that the combination of these two methods is capable of producing a more objective, effective, and accurate selection process. The developed system is expected to assist educational institutions in determining scholarship recipients in a targeted and transparent manner.